Investigation into mitochondrial function and energy metabolism and their connectivity with protumourigenic cellular proceses in Barrett's oesophagus - Phelan, James (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2016)
Contemporary clinical management of Barrett’s oesophagus has highlighted the lack of accurate predictors of neoplastic progression. Currently all Barrett’s patients undergo surveillance, however, only a subset of patients progress to oesophageal adenocarcinoma (OAC). Understanding the biology of why only a subset of these patients with Barrett’s oesophagus progress is a major clinical challenge. Abnormal mitochondrial function has long been linked with the development and progression of various cancers. Transitioning from a normal squamous cell to a malignant cancer cell is a multi-step pathogenic process which includes interactions between cancer-associated gene activation, metabolic reprogramming and tumour-induced changes in the microenvironment. The aim of this Ph.D thesis was to characterise mitochondrial function and energy metabolism across the Barrett’s disease sequence, to assess if markers of metabolism could have diagnostic potential and to further investigate the connection between metabolism and other key cellular processes activated in the Barrett’s tissue microenvironment, known to be previously linked with disease progression. Methods: PCR microarrays were employed to identify gene changes associated with mitochondrial function and mitochondrial energy metabolism in Barrett’s, dysplastic and OAC cells in-vitro. Upon identification, genes were validated in cell lines in-vitro and using in-vivo patient samples across the metaplastic-dysplastic-OAC disease sequence. Functional assessment of mitochondrial function genes were examined through a siRNA knockdown approach. Surrogate protein markers of oxidative phosphorylation (ATP5B/HSP60) and glycolysis (GAPDH/PKM2) were immunohistologically assessed across the metaplastic-dysplastic-OAC disease sequence in-vivo using tissue microarrays. Real-time metabolic profiles were challenged using Seahorse technology. The effect of the bile acid deoxycholic acid (DCA), proton pump inhibitors, antioxidants and a novel small molecule inhibitor (Quininib) on the modulation of cellular energetic was additionally assessed. The link between energy metabolism and other key cellular processes (inflammation, hypoxia, p53) in the Barrett’s oesophagus microenvironment was examined immunohistologically by assessing the expression of surrogate markers (IL1β/SERPINA3, HIF1α, p53) of these processes in cell lines in-vitro, in tissue microarrays in-vivo and in Barrett’s ex-vivo explant tissue. Furthermore, a transgenic mouse model of Barrett’s oesophagus was utilised to elucidate if IL1β overexpression and changes in dietary lifestyle could modulate oxidative phosphorylation, glycolysis, HIF1α and p53 thereby potentially promoting disease progression in Barrett’s oesophagus. Results: PCR microarrays identified 4 mitochondrial function genes (BAK1, FIS1, SFN, CDKN2A) and 3 mitochondrial metabolism genes (ATP12A, COX4I2, COX8C) differentially expressed across the metaplastic-dysplastic-OAC sequence in-vitro. Upon in-vitro validation of these gene targets, all genes exhibited differential expression profiles in in-vivo patient material. Altered expression was specific to Barrett’s tissue compared to matched normal adjacent tissue. siRNA knockdown of the BAK1, FIS1 and SFN genes resulted in significant decreases in mitochondrial membrane potential in Barrett’s cells and altered metabolic profiles in OAC cells in-vitro. We also demonstrate significant increases in the metabolic markers ATP5B, HSP60, GAPDH and PKM2 in epithelial tissue across the metaplastic-dysplastic-OAC sequence in-vivo. In addition, we show that the oxidative metabolism marker, ATP5B, segregated Barrett’s non progressors and progressors to neoplastic progression in first time surveillance biopsy tissue. Moreover, Seahorse analysis of oxidative metabolism in Barrett’s cells illustrate that Barrett’s cells rely significantly more on oxidative metabolism than to OAC cells. We also show that DCA decreases oxidative phosphorylation in Barrett’s cells, however, increases both metabolic pathways in neoplastic cells in-vitro. Moreover, DCA treated Barrett’s and OAC cells supplemented with the antioxidant EGCG exhibit significantly lower levels of oxidative phosphorylation and glycolysis respectively. The proton pump inhibitor lansoprazole and Quininib also exhibited anti-metabolic potential. Furthermore, we show that energy metabolism is linked with inflammation, hypoxia, p53 and obesity in the Barrett’s tissue microenvironment in-vivo and ex-vivo. Using a transgenic mouse model of Barrett’s oesophagus, we demonstrate that induction of inflammation through IL1β manipulation and a high fat diet can modulate the expression levels of GAPDH, ATP5B, p53 and HIF1α. Discussion: This Ph.D thesis demonstrates, for the first time, that changes in mitochondrial function, oxidative phosphorylation and glycolysis play central roles in disease progression in Barrett’s oesophagus. This thesis also identifies a marker of oxidative phosphorylation, ATP5B, with potential clinical utility in segregating those Barrett’s patients at higher risk of neoplastic progression. The in-vivo and ex-vivo findings demonstrated in the Barrett’s tissue microenvironment in patients and also in mice show that energy metabolism and its associated processes could potentially support disease progression in Barrett’s oesophagus, thereby highlighting future potential therapeutic opportunities in the field.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin